Analysis Of The Influence Of Digital Marketing Using Facebook Social Media On Increasing Sales At Omah Kelinci Farm In Lubuklinggau City - Riswandha Imawan Lingga; Rian Oktavianie; Anggia Syafitri; Fitri Yanti; Yayuk Marliza; Dina Nellysa (Universitas Dehasen Bengkulu, 2026)
The purpose of this study is to analyze the influence of Facebook usage on increasing sales in rabbit farms. The development of digital technology provides significant opportunities for livestock businesses to expand their markets. Social media, particularly Facebook, can be utilized as a means of promotion and communication between sellers and buyers. This research method used a descriptive qualitative approach with observation and interview techniques. Observations were conducted on rabbit farm marketing activities on Facebook, while in-depth interviews were conducted with farmers and several buyers. The results showed that Facebook usage had a positive impact on increasing sales, both in terms of the number of new customers, expanding market reach, and increasing interaction with consumers. Facebook has proven to be an effective, affordable, and easily accessible digital marketing medium for small businesses in the rabbit farming sector.